Analisis Akad Muzaraah terhadap Praktik Paroan Sawah dalam Meningkatkan Kesejahteraan Petani (Studi pada Desa Sarimulyo Kecamatan Sukaraja Kabupaten Seluma) - Shelly Nevrianti; Katra Pramadeka; Khairiah Elwardah (Universitas Muhammadiyah Surabaya, 2025)
The purpose of this study is to examine the practice of paroan sawah (sharecropping) in improving farmers’ welfare and to analyze its conformity with the principles of the muzaraah contract in Islamic economics. This research employs a descriptive qualitative method with a field study approach. Data were collected through interviews, observations, and documentation involving ten informants, consisting of five landowners and five tenant farmers in Sarimulyo Village, Sukaraja District, Seluma Regency. The results show that the sharecropping system in Sarimulyo Village is carried out traditionally based on verbal agreements between landowners and farmers. The distribution of yields generally follows a 1:1 or 2:1 ratio depending on the contribution of capital and production costs. This practice reflects mutual trust, social justice, and cooperation values, as described by Koentjaraningrat in his theory of agrarian social systems. However, from the perspective of Islamic law, this practice does not fully comply with the principles of muzaraah because there is no written agreement, the distribution of yields is not entirely transparent, and the sharing of production costs tends to be unequal. In terms of welfare, the sharecropping system helps farmers meet their basic household needs, although it has not yet ensured sustainable economic improvement.